The Incarnational Sense of God’s Mercy - Woźniak, Jakub Józef; Śledziewski, Sławomir (Studia Warmińskie, 2020)
The mercy of God who comes towards man is often equated with the event of the Passover, of Jesus’s suffering and death, where his love of man reaches its fullness. As a result, we often seem to forget about the beginning of God’s presence amongst men, the beginning which makes this presence tangible. His Incarnation is a manifestation of God’s love and mercy for us, a coming forward of the Other towards man, towards his sin. This paper undertakes to portray the sense and the need of the Incarnation. It discusses the terminological meaning of the word “incarnation” and outlines its Biblical references. Furthermore, it explores the meaning of God’s “self-abasement,” the motives and effects of the Incarnation and the connection between the Incarnation and the Passover.